Pressure relief for drilling (trenching) and support technology in deep soft rock tunnels - Ling, Yang; Ying, Xu (Frontiers in Earth Science, 2024)
Controlling surrounding rock stability in deep soft rock tunnels solely by increasing the support strength is challenging. The key areas where the surrounding rock of a roadway is prone to “instability” should be treated with comprehensive measures, such as drilling to relieve pressure, grouting of the surrounding rock, floor trenching technology, and secondary support, to achieve overall stability of the roadway surrounding rock. In this paper, based on a typical straight wall semi-circular arch roadway project in the Huaibei mining area of Anhui Province, mechanical parameters, such as cohesion, internal friction angle, Poisson’s ratio, and elastic modulus of the surrounding rock, were measured. Displacement stress distribution in surrounding roadway rock were simulated and analyzed using FLAC 3D, and the key parts of the surrounding rock prone to instability under the original roadway support conditions were determined. A suitable arrangement and parameters of the borehole pressure relief in the side roadway, floor grouting, floor trenching, and floor bolt secondary support were selected. Engineering measurements indicated that the engineering techniques were successful. It provided a significant reference for the comprehensive management and treatment of the surrounding rock stability in deep soft rock roadway on a global scale.